Stability of cooperation in the international climate negotiations - An analysis using cooperative game theory - Kersting, Jan (KIT Scientific Publishing, 2017)
International cooperation on greenhouse gas emission reductions is needed to avoid dangerous climate change. This work analyses the stability of global cooperation on climate change using cooperative game theory. Numerical and theoretical models are applied to evaluate the impact of several real-world properties. It is shown that the introduction of these properties into the game-theoretical model substantially affects the results and can make global climate cooperation unstable.